2022
DOI: 10.1002/alz.12823
|View full text |Cite
|
Sign up to set email alerts
|

Improving generalizability and study design of Alzheimer's disease cohort studies in the United States by including under‐represented populations

Abstract: The poor generalizability of clinical research data due to the enrollment of highly educated, non-Latinx White participants hampers the development of therapies for Alzheimer's disease (AD). Black and Latinx older adults have a greater risk for dementia, yet it is unclear how health-care disparities and sociocultural factors influence potential AD therapies and prognosis. Low enrollment of under-represented populations may be attributable to several factors including greater exclusion due to higher rates of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…As with ADNI, which makes all data available to requestors, the BHR has freely shared data with interested investigators. Our data sharing has led to a number of publications 15–44 . The BHR data are extremely large and complex, especially due to various changes that are made to add or remove various features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As with ADNI, which makes all data available to requestors, the BHR has freely shared data with interested investigators. Our data sharing has led to a number of publications 15–44 . The BHR data are extremely large and complex, especially due to various changes that are made to add or remove various features.…”
Section: Discussionmentioning
confidence: 99%
“…A number of local and national US AD‐related registries including the Alzheimer's Prevention Registry 7 and the Alzheimer Prevention Trial (APT) webstudy 8,9 exist, and differ in format and purpose 10–14 . Launched in 2014, the Brain Health Registry (BHR) is an online platform for the recruitment and assessment of participants for aging research 15–45 . By amassing a large pool of prequalified participants, the BHR aims to make clinical trials and neuroscience research studies more efficient and innovative.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous, complex factors contributing to the lack of inclusion of these groups in research, including failure of researchers to gain trust in these communities due to a legacy of unethical treatment, higher rates of comorbidities among these groups, failure of investigators to share information about studies with these groups, time burden of participation, issues with study design, and structural factors. 34,35 Frameworks such as community-engaged research have shown promise for increasing inclusion and engagement of minoritized communities, such as Black and Latino individuals, in ADRD research. [35][36][37] Several initiatives are now underway in BHR to improve participation of minoritized groups.…”
Section: Discussionmentioning
confidence: 99%
“…11 Assumptions based on research in which the majority of individuals are White may not provide appropriate insight into racial and ethnic minority populations in the US. 12,13 In the search for terminology to aid communication with all individuals living with dementia and their families and for broad communication with the public, careful testing with attention to race and ethnicity and culture is necessary. 8 A more comprehensive data collection is planned for the next phase of this work, including more robust qualitative data, to ensure that input is obtained from multiple types of patients and caregivers.…”
Section: Racial and Ethnic Diversity And Inclusion: Focus Groupsmentioning
confidence: 99%
“…The qualitative data support prior research indicating that term preferences and usage differ across racial and ethnic groups . Assumptions based on research in which the majority of individuals are White may not provide appropriate insight into racial and ethnic minority populations in the US . In the search for terminology to aid communication with all individuals living with dementia and their families and for broad communication with the public, careful testing with attention to race and ethnicity and culture is necessary .…”
Section: Nature Of the Problemmentioning
confidence: 99%